Single‐nucleotide polymorphism in chronic rhinosinusitis: A systematic review - Antonino, Maniaci; Nicolò, Musso; Jerome Renee, Lechien; Federico, Merlino; Chiara, Viglianisi; Stefano, Stracquadanio; Maria, Santagati; Salvatore, Cocuzza; Antonio, Bonanno; Calvo‐Henriquez, Christian; Stefania, Stefani; La Mantia, Ignazio (Clinical otolaryngology, 2022)
Objectives We performed a systematic review on single‐nucleotide polymorphisms and risk‐related chronic rhinosinusitis. Design and Setting A comprehensive review of the last 20 years’ English language literature regarding chronic rhinosinusitis and single‐nucleotide polymorphisms was performed. We included in the synthesis all the papers reporting gene variation implicated in the pathogenesis of chronic inflammation and polyps. Results We found 12 papers with 9127 patients, of which 2739 CRS cases and 6388 controls. The major comorbidities reported related to chronic rhinosinusitis were atopy in 4555 (49.9%), asthma in 4594 (50.33%), Samter Triad in 448 (4.9%) and eosinophilia in 391 subjects (4.28%). Conclusion Our systematic review revealed the major SNPs significantly associated with chronic rhinosinusitis and the specific pathways involved. Given the presence of different extraction methods and samples sequencing, further studies with larger courts are necessary to identify significative single‐nucleotide polymorphisms.